Age-related changes in the allocation of spatially directed focal attention. Issue 5 (2nd September 2020) - Mańkowska, Aleksandra; Heilman, Kenneth M.; Williamson, John B.; Michałowski, Jarosław; Harciarek, Michał
ABSTRACT: Objectives: Leftward deviation on a horizontal line bisection test (pseudoneglect) might be induced by right hemispheric dominance for mediating spatial or global attention, or a hemispheric asymmetry in the ability to spatially disengage attention. With aging, this leftward bias is reduced, likely due to the aging-related deterioration of right hemisphere mediated functions (right hemi-aging) or hemispheric asymmetry reduction in old adults (HAROLD). Methods: Forty-seven healthy adults divided into younger and older groups performed a modified Posner spatial-attentional task. Results: Overall, younger individuals responded faster to left than right-sided imperative stimuli. In contrast, older participants did not reveal a right-left asymmetry to imperative stimuli. The younger group also revealed a strong inverse relationship between the reaction time to right valid cues and the leftward attentional bias while performing the line bisection task (pseudoneglect). Conclusions: Our results provide support for both the right hemisphere spatial-attentional dominance hypothesis of pseudoneglect and the right hemi-aging hypotheses.